'Do Not Attempt Cardiopulmonary Resuscitation' discussions at the point of discharge: a case note review of hospice practice following local integrated policy implementation. Issue 2 (1st September 2011) - Hall, Charlie Christopher; Mark, Kathleen; Oxenham, David; Spiller, Juliet Anne
Abstract : Background: An integrated 'Do Not Attempt Cardiopulmonary Resuscitation' (DNACPR) policy was implemented across Lothian in 2006 (for ease of reading the terminology 'DNACPR' has been used throughout the paper where the original Lothian Policy used 'DNAR'). Patients were, for the first time, able to be discharged home with their DNACPR form after discussion about cardiopulmonary resuscitation (CPR). Aims: To ascertain the number of patients who, following a discussion, were discharged with a DNACPR form and the reasons for not holding discussions with certain patients. Methods: Two retrospective case note reviews of 50 patients discharged over two 4-month periods (2007 and 2009). Results: There was a high proportion (78–80%) of CPR discussions for patients discharged from the hospice. Reasons for not discussing CPR were: potential for excess distress (10–12% 2007 and 2009) and lack of time (4% both years). Of those discussing CPR on discharge, 90% took forms home in both years. The reasons patients did not take forms home were: form not taken in error (two patients in 2007); patients refusing a form at home (one and three patients in 2007 and 2009); form to be arranged by general practitioner and one incomplete discussion. The proportion of patients with forms already at home increased from 10% (2007) to 28% (2009). Conclusion: It is possible to discuss CPR with a high proportion of hospice patients prior to discharge from a hospice. Following the introduction of an integrated policy, more patients have DNACPR forms prior to admission. Most patients receiving specialist palliative care find DNACPR discussions acceptable and understand the benefits of having a DNACPR form.